Full-Scale Tests To Evaluate Lateral Pile Resistance At The Edge Of A Slope - Artak D. Mirzoyan (Deep Foundations Institute, 2007)
Pile foundations near the edge of a slope are often required to resist lateral loads. This is particularly important for piles at abutments of bridges. However, very few full-scale tests are available that compare the effect on lateral resistance of piles installed in sloping ground to piles installed in horizontal ground. To investigate the effect of a slope on lateral pile resistance, three full-scale lateral load tests were performed on an instrumented steel pipe pile. For the first test, the pile was laterally loaded in horizontal ground; in the second test, the pile was at the crest of a 30º downward slope; and for the third test, the pile was located three pile diameters from the crest of a 30º slope. The soil around the pile consisted of well-graded clean sand (concrete sand) and was compacted to 95% of the modified Proctor maximum unit weight in all three tests. Lab and in-situ direct shear tests indicated that the friction angle of the sand was approximately 39 degrees. The pile was instrumented with strain gauges so that the bending moment versus depth profile could be determined. Pile head load, deflection and rotation were also measured. Based on the load versus deflection curves, the presence of the slope resulted in a decrease in lateral resistance of about 20% for the pile at the crest of the slope and 8% for the pile at 3D from the crest of the slope relative to the pile in horizontal ground. The presence of the slope also resulted in an increase in the maximum moment of 29% and 20% for the piles at the slope crest and at 3 pile diameters from slope crest, respectively. Analyses using LPILE with the measured friction angle significantly underestimated the lateral resistance for the horizontal soil profile. After calibrating the model with the response of the pile in horizontal sand, analyses including the slope still underestimated lateral resistance by about 20%.